Genet ic Variability and Divergence Studies for Gall Midge Resistance and Yield Components in Rice (Oryza sativa L.) - Srinivas, B.; Chandramohan, Y.; Thippeswamy, S.; Padmaja, D. (International Journal of Bio-resource and Stress Management, 2023)
Eighteen rice genotypes were evaluated for studying genetic parameters and genetic divergence for yield contributing characters and gall midge resistance at Regional Agricultural Research Station, Jagtial, Telangana. Analysis of variance revealed the presence of significant variability in experimental material for all the traits under study. Heritability estimates and genetic advance values indicated that percent of galls, effective bearing tillers plant-1, 1000 grain weight and number of grains panicle-1 were predominantly governed by additive genes which could be improved through proper selection in desirable direction, whereas, non additive genes played dominant role in the inheritance of days to 50% flowering, plant height and panicle length which could be improved through heterosis breeding. Mahalanobis D2 analysis distributed 18 genotypes into three clusters with cluster I containing maximum number of genotypes (14). Maximum inter cluster distance (10.48) was observed between cluster II and cluster III indicating wider genetic diversity, hence, crosses involving parents belonging to these clusters likely to produce wide variability and transgressive segregants with high heterotic effects. Genotypes JGL 19607, JGL 21820, JGL 3844 (cluster II) and JGL 23745 (cluster III) exhibited least gall midge incidence which could be utilized as parents in developing gall midge resistance genotypes. 1000 grain weight and days to 50% flowering were contributed maximum (75.16%) to the total divergence which could be given due importance during hybridization and selection in segregating populations.